Voltammetry in the presence of ultrasound: A novel sono-electrode geometry - Eklund, J; Marken, F; Waller, D; Compton, R (1996)
A new sono-electrode geometry is discussed in this paper, in which a square electrode of millimetre dimensions is placed perpendicular to a 20 KHz ultrasonic horn probe, its centre being some 30-40 mm distant from the surface of the tip of the ultrasonic horn. It is shown that the mass transport of electroactive material to the electrode can be approximately described by that of a convective flow over a stationary plate through comparison of the experimental results with theoretical data obtained via the analytical solution of the mass transport equations describing this model. This novel sono-electrode geometry is compared with other more popular geometries introduced in the recent sonoelectrochemical literature and the relative merits of these sonotrodes are discussed with respect to their mass transport characteristics. Copyright © 1996 Elsevier Science Ltd.